Accountability of Temporary Land Deed Official Not Included as Defendants in Deed Revocation Rulings: Study of Verdict Number 601/Pdt.G/2020/Pa.Tnk. - Nilna Firkhana Soraya; Sukarmi; Patricia Audrey Ruslijanto (Faculty of Law, University of Jember, Indonesia, 2025)
This study examines the role of the Temporary Land Deed Official (PPATS) in the issuance of legally defective deeds. The case, as adjudicated in Verdict Number 601/Pdt.G/2020/PA.Tnk, indicates that the PPATS was neither designated as a Co-Defendant nor held materially liable to the disputing parties. In the court's consideration, the judge reasoned that the PPATS was not directly implicated in the case since the Grant Deed (Akta Hibah) was not annulled, but rather the